Concept of Geographical Formation: theory and method (Huellas, 2021)
The concept of "geographical formation" is postulated as a necessary theoretical and methodological overcoming of the concept of "geographical space" to designate and address the objects and problems of geography, in order to simultaneously respond to epistemological and practical demands.
Keywords: geographic formation; social training; geohistoricity; territorial dialectic; critical geography